Making sense of the dollar exposing dangerous myths about trade and foreign exchange - Chandler, Marc 1961- (Bloomberg Press, 2009)
"Making Sense of the Dollar explores the many factors--trade deficits, the dollar's role in the world, globalization, capitalism, and more--that affect the dollar and the U.S. economy and lead to the inescapable conclusion that both are much stronger than many people suppose"--Provided by publisher.